Field reports form for submitting seasonal observations of Iowa birds, Eloise Armstrong and Eugene Armstrong, fall 1991 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1991)
List of birds and locations contributed by Eloise Armstrong and Eugene Armstrong. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed